Práxis corporal eco-relacional e a decolonialização do ambiente educativo: a juventude semeando afetos no chão da escola de ensino médio - Lima, Ana Natália Duarte (2024)
This research analyzes the repercussions of Eco-relational body praxis in building an affective and decolonial school environment for better coexistence and teaching and learning among the high school student community, through an intervention in a state public institution. It arises from the problematization of the school environment, whose relationships are often marked by denial, disqualification, disputes and violence that harm this coexistence, making it impossible to create an affective educational environment that is stimulating and enhances teaching and learning. These harmful relationships are the result of colonializing micro-social processes, since educational practices are generally geared towards the rational and instrumental dimensions at the service of maintaining neoliberal logic, perpetuating relations of subalternity and indifference in this environment. The aim is to improve the perception of the body that we are through reflexive, sensory, motor and affective experiences in the act of learning and teaching as dialogical practices enhanced by the Eco-Relational Perspective - PER (Figueiredo, 2007). This offers intercultural and multidimensional educational epistemologies and methodologies that encompass human complexity. With a qualitative approach, through Engaged Research (Figueiredo, 2004), we built affective-relational practices through the Dialogic Circle and Biodanza exercises. Its foundations include the strengthening of social ties and the creation of bonds, integrity, appreciation and respect for the lives, cultures, traditions, histories and spaces where they live. The data collection instruments were participatory observation, audio and video recording, photographs and interviews, interpreted using Discursive Textual Analysis (Moraes, 2003). I advocate a decolonial educational practice that rescues other dimensions (sensitive, emotional, sentimental, intuitive and spiritual) in an attempt to convert the paradigm of violence, pain and lack into collective references of pleasure, power, joy and affection. The experience in the field allowed us to develop essential aspects at school: the bodily knowledge/learning, collectivity and joy. These aspects have been fundamental to our educational experiences since the beginning of the cycles. Thus, the actions and reflections developed from an Eco-relational body praxis make it possible to problematize the fragmentation of life by the hegemonic logic and empower new affective mobilizations as other ways of giving new meaning to feeling, thinking, being and being in the world and with the world.